Factors of Potential Forms of Creative Transformation in Urban Speech: Classification Approach (Proceedings of Southern Federal University. Philology, 2018)
Natalya Yu. Timofeeva (Simferopol, Russian Federation)Under creative speaking grammatical and extra-linguistic factors are interplaying. Therefor classification of such processes is still relevant. Potential words as the system determined type of ad-hock creativity can be classified according to the grade of deviation, concerning as derivation model components, as non-linguistic factors action, influence of social context. Each model has more or less strict components parameters: formant meaning and definite part of speech for stem. During communication speaker can actualize any of the forms, which one lexical group paradigms have. Created form can appear despite the model maturity and this is the way of its occasionality rising. If there is no lacuna in a model paradigm so some form, duplicating another one, reveals special pragmatic need of the speaker. Considering distance between system norms and real speech circumstances, we are able to fix difference among potential words as more or less occasional. So we get a scale with conventional numerical indication of the occasionality growth – from zero to one with a half index for cases of incomplete characteristic. The last one means light deviation of the model: formant meaning variation or part of speech shifting for stem, or weak perlocution in the structure of intention. Zero index marks model safety, available system gap for the potential form and absence in the speech act any perlocution or social ranging. The index “one” fixes opposite characteristic: a deep model deviation (e.g. stem structure breach), system gap absence for the potential form or duplicating paradigm fragment and explicit under the speech act perlocution or social ranging. The scale can be used as the base for forecasting of the usage “future” for each potential word, if the absolute zero and absolute one will be considered as the indexes of system integration and social demand.Key words: creativity, potential word, derivation model, formant, language system, occasionality, pragmatic factor, social ranging, word usage.DOI 10.23683/1995-0640-2018-1-134-141